HUBUNGAN KESEHATAN SPIRITUAL DENGAN HIPERTENSI PADA LANSIA DENGAN PENDEKATAN TEORI KEPERAWATAN VIRGINIA HENDERSON DI PANTI LANJUT USIA HARAPAN KITA PALEMBANG - WM, TRILIA (Masker Medika, 2021)
Background: Virginia Henderson introduces a definition of nursing (definition of nursing). Henderson also developed a nursing model known as "The Activities of Living". In this model there are fourteen basic needs of Virginia Henderson which can be classified into four components, one of which is a component of spiritual health. Spiritual health includes attitude, meaning and spiritual support with a better cardiovascular condition. Diseases related to spiritual health that can threaten and hinder the spiritual development of the elderly, one of which is hypertension. Research objective: to see the relationship between spiritual health and hypertension. Methods: This study used a cross sectional design. The sample is elderly with hypertension 32 respondents. Data were collected using a questionnaire. Data were analyzed using Chi square test with a significance value of p value <0.05. Result: positive category spiritual attitude 81.3%, good spiritual meaning 84.4%, bad spiritual support 81.3%, respondents with mild hypertension was 53.1% and there was no relationship between spiritual health and hypertension. Conclusion: Spiritual health does not have correlation with hypertension in the elderly. Key words: spiritual health, hypertension and the elderly